FEATURES OF DEVELOPMENT OF PHYSICAL QUALITIES IN THE PROCESS OF SPORTS TRAINING OF STUDENTS - Laylo, Shakhriddinova; Norpulat, Bobomurodov; Ahmad, Mukhametov (International Journal of Psychosocial Rehabilitation, 2020)
The content of the article reveals the essence of education of the basic physical qualities of athletes, the necessary competitive and training activities. Valuable recommendations are given on the development of strength, speed, endurance, etc.